Effect of Tree Canopy Cover on Grass Species in Nigerian Guinea Savanna - Muoghalu, Joseph Ikechukwu; Isichei, Augustine Onwuegbukiwe (2014)
The effect of tree canopy cover on the yield, crude protein (CP), and fibre content of grass species in the Nigerian Guinea savanna was studied. The following grass species, Andropogon gayanus, Hyparrhenia involucrata, Hyparrhenia smithiana, Pennisetum polystachion, Rottboellia cochinchinensis, and Setaria barbata occur more under tree canopies than in the open. The overall yield under tree canopy and in the open was influenced by the proportionate contribution .of these species to the total yield. Grass yields were significantly higher under canopies provided by trees taller than 7 m than under shorter canopies. The difference between percentage CP, fibre, and lignin in plants growing under tree canopies and those in the open were not significant.